The effect of brand value proposition and product positioning on purchase intention of Traveloka users in Indonesia - Sardina Sobeukum; Yandri Samuel Augusteyn; Merlin Kristen Ratu Elo (PT Aksara Indo Rajawali, 2026)
Purpose – This study aims to analyze and explain the influence of Brand Value Proposition and Product Positioning on the Product Positioning of Traveloka app users in Indonesia. Design/methodology/approach – This study employs a quantitative survey approach. Data were collected via an online questionnaire from 100 respondents using non-probability sampling techniques. The data analysis technique used was multiple linear regression to test the relationships among the study variables. Findings – The results indicate that both Brand Value Proposition and Product Positioning have a significant and positive influence on users' Product Positioning. These findings indicate that strengthening brand value and the accuracy of Product Positioning in consumers' minds effectively drives Product Positioning on digital platforms. Research limitations – The limitations of this study lie in the small sample size and its focus on Indonesia alone; therefore, generalizing the results to a global context requires caution. Implications – In practical terms, Traveloka's management needs to continue refining its marketing communication strategies to highlight the uniqueness of its services and strengthen its market position. Theoretically, this study contributes to the literature on consumer behavior in the digital economy. Originality – This paper offers new insights by integrating value proposition and Product Positioning variables into a single empirical model within the dynamic online travel agency (OTA) industry in Indonesia.